1993
DOI: 10.1161/01.res.73.5.906
|View full text |Cite
|
Sign up to set email alerts
|

Renal afferents signaling diuretic activity in the cat.

Abstract: Mechanoreceptors and chemoreceptors have been identified inside the kidney, but their functional role is still largely unclear. The aim of this study was to investigate whether changes in urine output could modify the discharge rate of renal afferent fibers. Experiments were performed in anesthetized cats in which afferent renal nerve activity (ARNA) was recorded by standard electrophysiological techniques from a centrally cut renal nerve. Arterial pressure, renal blood flow velocity, urine flow rate, and rena… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0

Year Published

1997
1997
2023
2023

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(23 citation statements)
references
References 17 publications
0
22
0
Order By: Relevance
“…As the increased afferent renal nerve activity was associated with contralateral diuresis and natriuresis, a role of renal mechanoreceptors in the control of body water and sodium balance has been suggested [4, 14, 151. In previous experiments, performed in anaesthetised cats [16], we have demonstrated that diuretic manoeuvres activate renal mechanosensitive fibres by increasing pelvic pressure, thus suggesting a role of renal mechanoreceptors in monitoring urine volume in the cat [16].…”
Section: Introductionmentioning
confidence: 77%
“…As the increased afferent renal nerve activity was associated with contralateral diuresis and natriuresis, a role of renal mechanoreceptors in the control of body water and sodium balance has been suggested [4, 14, 151. In previous experiments, performed in anaesthetised cats [16], we have demonstrated that diuretic manoeuvres activate renal mechanosensitive fibres by increasing pelvic pressure, thus suggesting a role of renal mechanoreceptors in monitoring urine volume in the cat [16].…”
Section: Introductionmentioning
confidence: 77%
“…Several studies have demonstrated that furosemide can directly activate the renal sympathetic nervous system (124), independent from the RAS (123). This could well be elicited by a change in the local micro-environment of the afferent nerve ending in the renal interstitium (52). Nevertheless, renal denervation did not affect the natriuresis evoked by furosemide acutely (146) in lambs or chronically (122) in rats under physiological conditions.…”
Section: Questions Pertaining To the Natriuretic Response To Furosemidementioning
confidence: 99%
“…Since the reflex pressor response and reflex increase in sympathetic nerve activity in response to stimulation of ARNA is severely blunted during anesthesia (Smits & Brody 1984;Faber & Gettes 1987;Janssen et a/. 1989b), the lack of correlation between increased ARNA and increased arterial pressure during furosemide diuresis in the study by Genovesi et a/. (1993) could be related to the use of anesthesia.…”
Section: Renal Mechanisms Involved In the Immediate Sympathoexcitatormentioning
confidence: 92%
“…In this study, furosemide stimulated prostacyclin release and increased cyclic GMP formation and since both actions were inhibited by a bradykinin type-2 receptor antagonist, the authors concluded that furosemide stimulates endothelial synthesis and release of kinins which in turn stimulates prostacyclin formation. Whereas this mechanism may be important for stimulation of sensory neurons (IX; Nerdrum et al 1986;Uchida & Murao 1974;Ohno et al 1984;Kopp & Smith 1993;Genovesi et al 1993), the direct vasorelaxant effect of furosemide on isolated arteries being endotheliumindependent suggests that endothelial kinin release is functionally of minor significance for direct arteriolar effects of furosemide. Whether furosemide stimulates kinin release in endothelium from venous vessels is unknown.…”
Section: Effects Of Furosemide On Systemic and Renal Hemodynamicsmentioning
confidence: 99%